Reimagining Christianity and Sexual Diversity in Africa - Ashwin Thyssen (African Journal of Gender and Religion (AJGR))
The recent publication by Adriaan van Klinken and Ezra Chitando, titled Reimagining Christianity and Sexual Diversity in Africa (2021), continues to garner much attention from the theological community. This publication is important on numerous fronts. At least two are noteworthy and inform the present appraisal. First, van Klinken and Chitando’s work speaks to the religious, particularly Christian, realities that beset contemporary Africa. Second, their work takes seriously the ways in which the lives of Africans are being rendered precarious because of the limited socio-political progress with regard to LGBT+ rights. This review article is offered taking seriously the ways in which LGBT+ lives are rendered precarious by the oppressive logic of forms of Christianity.